Effect of per os administration of fucoxanthin alcoholic and oil extracts to Balb/c mice on biochemical parameters and serum cytokine level - А. Р. Lykov; R. G. Gevorgiz; S. N. Zheleznova; L. N. Rachkovskaya; О. V. Poveshchenko (Сибирский научный медицинский журнал, 2024)
Microalgae are a source of various biologically active substances, including carotenoids. One of the carotenoids of diatom microalgae is fucoxanthin, which has antioxidant, antimicrobial, antitumour and anti-inflammatory properties that can be used in the treatment of a wide range of human and animal pathologies. The aim of the study was to investigate the effect of alcohol and oil extract of fucoxanthin on biochemical parameters and levels of serum cytokines in mice during intragastric administration. Material and methods. Fucoxanthin extracts from the microalga Nanofrustulum shiloi were used. Mice of Balb/c strain were intragastrically administrated with 0.5 ml of oil (500 μg/ml) or alcoholic extract of fucoxanthin (187.5 μg/ml), mice in the comparison group were given 0.5 ml of olive oil or 45% ethyl alcohol once a day within 5 days. On the 8th day, blood serum was obtained and the level of albumin, triglycerides, cholesterol, low (LDL) and high density lipoproteins (HDL), urea, uric acid, creatinine, aspartate (AST) and alanine aminotransferases (ALT), lactate, stable nitric oxide (NO) metabolites (nitrites), cytokines (IL-1β, IL-6, IL-10, TNF-α, IFN-γ) was determined using ELISA with photometric detection. Results and discussion. In the comparison group, ethyl alcohol promoted an increase in serum triglyceride, cholesterol, LDL, HDL, ALT, AST, nitrite, IL-10, IFN-γ and TNF-α content compared to intact animals. Fucoxanthin alcoholic extract administration increased the level of LDL, HDL, uric acid, TNF-α and decreased albumin, cholesterol, uric acid, creatinine, ALT, AST, IL-6 content compared to control. The olive oil group showed a decrease in serum triglycerides, cholesterol, urea, uric acid, ALT and AST content but an increase in LDL, HDL, nitrite level compared to the control. Administration of fucoxanthin oil extract to animals decreased albumin, triglycerides, cholesterol, HDL, uric acid, ALT, AST, lactate, IL-6, IL-10 compared to control. Conclusions. Thus, it was discovered that fucoxanthin in Balb/c mice contributes to a decrease in hepatic synthetic function, as evidenced by the change in the concentration of albumin, triglycerides, uric acid), influences energy metabolism (creatinine, lactate), cell membrane stability (cholesterol, LDL, HDL), serum transaminase activity, pro- and anti-inflammatory cytokines content.